Authority and the Problem of Other Minds in Shakespeare's 'Henriad'. - Pensky, David Nathan (Early Modern Literary Studies, 2023)
The article focuses on the divisive interpretations of Prince Hal's character in the Henriad plays, particularly in "Henry V," and the question of whether he is a heroic figure uniting England or a manipulative scoundrel. The author explores the problem of interpreting Hal's character through the lens of the "problem of other minds," considering the opacity of the king's mind and the shifting theories of authority in the plays.